Implementasi Mix Method Dalam Pembelajaran Kosakata Bahasa Arab Pada Siswa Kelas IV Madrasah Ibtidaiyah Muhammadiyah Gading 1 Klaten - Utami, Aprillia Putri (Universitas Islam Ahmad Dahlan Sinjai, 2025)
Vocabulary mastery (mufradāt) is one of the essential components in learning Arabic, particularly at the elementary level in Islamic schools. However, Arabic language learning in Madrasah Ibtidaiyah often encounters several challenges, including low student motivation and the use of monotonous teaching methods. This study aims to analyze the implementation of a mix method that integrates singing activities, interactive quizzes, and poster creation to improve Arabic vocabulary mastery among fourth-grade students of Madrasah Ibtidaiyah Muhammadiyah Gading 1 Klaten in the 2025/2026 academic year. This research employed a qualitative descriptive approach. The research subjects consisted of 25 students from class IV E. Data were collected through observation, interviews, and documentation, and analyzed using the interactive analysis model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the mix method creates a more engaging and participatory learning environment. Singing activities help students memorize vocabulary through rhythm and repetition, interactive quizzes increase student participation in the learning process, while poster-making activities strengthen students’ understanding through visual and creative approaches. The integration of these activities enhances students’ engagement and facilitates their ability to remember and pronounce Arabic vocabulary. Therefore, the mix method can serve as an effective alternative teaching strategy to improve Arabic vocabulary mastery among elementary school students. The novelty of this study lies in the application of the mix method that integrates three main components: vocabulary singing, interactive quiz, and mufradat poster making simultaneously within a single integrated learning model for Arabic language instruction at Madrasah Ibtidaiyah, in contrast to previous studies that tend to examine only one method or one type of medium in isolation